Effect of Metadoxine on Chronic Primary Hepatopathies in Canines: Number of Cases - Paula María Bermúdez-Duarte; José Alfredo Rivera-Rojas (Revista MVZ Cordoba)
Objective. To evaluate the effect of Metadoxine on paraclinical, ultrasound, and histopathological findings in canines with primary hepatopathies through a number of cases. Materials and Methods. Seven dogs aged 2 to 14 years with mild to moderate clinical signs of primary hepatopathy, abnormal bile acids, increased ALT or ALP values three times above the upper range for 4 weeks, underwent ultrasound evaluation and ultrasound-guided Tru-Cut liver biopsy to confirm hepatopathy according to the histological classification of the WSAVA. Prior to the biopsy, they were required to have fibrinogen >100 mg/dL, platelets >100 cells x 103/µL, and prothrombin time <11.5 seconds. Once the histological diagnosis was confirmed, they received metadoxine at 17±11.35 mg/kg every 12 hours for 4 weeks. Clinical, paraclinical, ultrasound, and histopathological follow-up was conducted at the end of this period. Results. A decrease in the occurrence of vomiting and anorexia was observed (p=0.03), a non-significant increase in ALT and ALP (p=0.84; p=0.43), a reduction in bile acids (p=0.4), and no change in ultrasound score (p=0.42) or histopathological diagnosis (p>0.05). Conclusions. Despite significant limitations, this number of cases provides preliminary observation suggesting that metadoxine may improve the clinical condition of dogs with liver disease without altering paraclinical, ultrasound, or histological variables; additional research with a Randomized Clinical Trial design is needed to propose metadoxine indication protocols for canines with hepatopathies in clinical practice.